Kontribusi Penyesuaian Diri Sebagai Alternatif Penurunan Stres Belajar Mahasiswa di Masa Pandemi Covid-19 - Basith, Abdul; Rahmawati, Indriana (FENOMENA, 2021)
The Covid-19 pandemic affects the quality of life of a person and society in general. Pandemics can cause social disruption, negative stigma, and excessive panic. Apart from economic activities, teaching and learning activities in schools and universities are also limited. Require all educators to carry out learning from home. Online learning replaces all conventional classroom settings, thereby expanding the reach of learning beyond boundaries, time, and space. However, online learning carried out from home poses various problems. The problems that arise include boredom and stress in education. This study determines the decrease in student learning stress by making adjustments. The Research was conducted on students with a total sample of 99 students. The hypothesis is that self-adjustment contributes to reducing student learning stress. Data were obtained by using questionnaires and documentation. The results showed that the hypothesis was accepted on the basis of the T-count value in the T-test received several of 5.309, where the value was smaller than the T-table value of 1.660, and the significance value was 0.000 less than the 0.05 significance level. For the large contribution, it is obtained from the Coefficient of Determination test with a score of 0.457 or 45.7% if it is a percentage, which means that the self-adjustment hypothesis contributes 45.7% to the decrease in learning stress for students of UINSI Samarinda and STAI Sangatta East Kutai.